Evaluation of acute postoperative pain management after living donor nephrectomy during the transition from open access to laparoscopic and minimally invasive robotic surgical approach - Amer Majeed; Noon E. Abdelgadir; Areej A.G. AlFattani; Bilal Tufail; Muhammad Shabbir; Sajjad Rasool; Basel A. Jobeir (Saudi Journal of Anaesthesia)
Background: Living donor nephrectomies (LDN) at our institution transitioned from open access to laparoscopic and, more recently, to a minimally invasive robotic surgical approach between 2019 and 2022. Concurrently, postoperative analgesia transitioned from regional anesthesia to intravenous patient-controlled analgesia (PCA) and eventually to simple analgesics with additional rescue analgesic agents, as needed, in accordance with individual physicians’ preferences. This retrospective study was designed to evaluate the impact of these changes on surgical practice on the analgesic requirements and effectiveness of postoperative pain management. Methods: Electronic records of all LDN cases operated between January 2019 and March 2022 were accessed, and a comparative analysis of patient demographics, surgical approach, duration of surgery, postoperative pain scores, and the analgesics administered within the first 48 h was performed. Results: LDN (n = 527) was performed via laparoscopic (n = 432, 82%), robotic (n = 87, 17%), and open (n = 8, 2%) approaches. All patients were administered regular paracetamol 1 g 6 hourly. IV PCA was used in 85% of cases, predominantly in the laparoscopic (99%) and open (75%) groups (LG and OG, respectively); in contrast, the robotic group (RG) was mostly treated without PCA (81.7%). A variety of analgesic techniques were employed for the remaining patients, including epidural (25% of OG) and rectus sheath/transversus abdominis plane (TAP) block (2% of LG). Additional rescue analgesics were administered to 98% of the patients; 92% of LG needed 1–3 analgesic agents, whereas all of the OG and 37% of RG needed 1–2 rescue analgesics. No correlation was found between patient demographics and surgery duration on pain scores or analgesic requirements. Conclusions: Robotic surgery was associated with the lowest postoperative pain scores and analgesic demand; laparoscopic resection was the most painful of all.